And Incidentally, the Score is Quite Beautiful’: – Work conceptual reflections on the phonographic remediations of Max Steiner’s symphonic film score for ‘Gone with the Wind’ (1939) as soundtrack album - Kaargaard Nielsen, Steen (Danish Yearbook of Musicology, 2008)
The article discusses key work-conceptual themes at play in the various re-mediations of the classic American symphonic film score as a phonographic product from the early formation of the soundtrack album in the 1950s and onward. Released between 1954 and 1996, the numerous soundtrack albums dedicated to film composer Max Steiner’s canonic score for David O. Selznick’s Gone with the Wind (1939), based on either the original optical music track recordings or later studio re-recordings, serve as an exemplary but also somewhat unique illustration throughout, as the historically evolving character of this phonographic sub-genre is pursued.